2017
DOI: 10.1016/j.jaci.2016.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis reveals clinically relevant atopy phenotypes in 2 birth cohorts

Abstract: LCA revealed a set of benign, symptomatic, and severe atopy phenotypes. The severe phenotype emerged as a latent condition with signs of a dysbalanced immune response. It determined high asthma risk through excessive sIgE production and directly affected impaired lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 32 publications
6
96
4
Order By: Relevance
“…Similar quantitative relationship has also been reported in relation to asthma severity and severe asthma exacerbations in children (23, 24). Notably, a recent report suggested that in severe pediatric asthma both allergen-specific IgE antibodies and skin prick tests should be carried out and quantified, as these tests are not always concordant in this specific population of patients (25).…”
Section: The Burden Of Atopy In Pediatric Asthmasupporting
confidence: 84%
See 2 more Smart Citations
“…Similar quantitative relationship has also been reported in relation to asthma severity and severe asthma exacerbations in children (23, 24). Notably, a recent report suggested that in severe pediatric asthma both allergen-specific IgE antibodies and skin prick tests should be carried out and quantified, as these tests are not always concordant in this specific population of patients (25).…”
Section: The Burden Of Atopy In Pediatric Asthmasupporting
confidence: 84%
“…Increasing data also show that the level of allergen-specific IgE antibodies and the size of skin test wheal to aeroallergens can better help identifying children at risk of preschool wheezing and subsequent asthma than a simple positive allergy test (2123). Similar quantitative relationship has also been reported in relation to asthma severity and severe asthma exacerbations in children (23, 24).…”
Section: The Burden Of Atopy In Pediatric Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…26 intensive care is also more frequently associated with food allergy 29 and food sensitization presents an increased risk of admission related to pollen exposure in girls. 26 intensive care is also more frequently associated with food allergy 29 and food sensitization presents an increased risk of admission related to pollen exposure in girls.…”
Section: And the Manchester Asthma And Allergy Studymentioning
confidence: 99%
“…Because clinical manifestations of transient wheeze and asthma (persistent wheeze) are indistinguishable in early life, childhood asthma cannot be diagnosed with certainty before the age of 5, even though most childhood asthma likely begins in the first 3 years of life [4]. The development of atopic sensitization to food and inhalant allergens in the first years of life significantly contributes to the development of asthma [57], but epidemiologic patterns of asthma and atopy differ: the prevalence of atopy rises from infancy to preschool age and then it reaches a plateau [7]. Infections with rhinovirus (RV) and respiratory syncytial virus (RSV) early in life are likewise strong determinants of subsequent asthma development [8,9].…”
Section: Introductionmentioning
confidence: 99%